DYNAMICS IN CHANGES OF FREE-RADIAL OXIDATION PROTEINS, REGENERATOR PROCESSES, MICROBIAL DISTRIBUTION AND NON-SPECIFIC IMMUNITY IN THE HOMOGENATES OF SCAR TISSUES AT DIFFERENT STAGES OF THE POSTOPERATIVE PERIOD - L.R. Krinichko; S.M. Grigorov (Проблеми екології та медицини)
The problem of excessive scar formation deserves a particular attention, primarily in the open areas of the human body, because the biochemical mechanisms of the regulation of collagenosynthesis processes after planned surgical interventions of the skin are not well-substantiated. The aim of the study was to optimize the prevention of pathological scars after surgical treatment of congenital neck cysts by determination of the dynamics of changes in biochemical parameters occurring in the neck skin at various stages of healing. It was proved that the combined use of PRF-clot at the intraoperative stage of prophylaxis and ceruloplasmin at the post-operative, in contrast to monotherapy with fibrin membranes, obtained from platelets-rich plasma caused a better functional and aesthetic result, which significantly improved the quality of life of patients in the early and late postoperative periods.